Effects of allicin supplementation on plasma markers of exercise-induced muscle damage, IL-6 and antioxidant capacity - Su, Q.-S.; Tian, Y.; Zhang, J.-G.; Zhang, H. (European Journal of Applied Physiology, 2008)
To investigate the effects of allicin supplementation on exercise-induced muscle damage (EIMD), interleukin-6 (IL-6), and antioxidative capacity, a double-blinded, placebo-controlled study was conducted in well-trained athletes. Subjects were randomly assigned to an allicin supplementation group (AS group) and a control group, and received either allicin or placebo for 14 days before and 2 days after a downhill treadmill run. Plasma creatine kinase (CK), muscle-specific creatine kinase (CK-MM), lactate dehydrogenase (LDH), IL-6, superoxide dismutase (SOD), total antioxidative capacity (TAC), and perceived muscle soreness were measured pre and post exercise. AS group had significantly lower plasma levels of CK, CK-MM and IL-6, and reduced perceived muscle soreness after exercise, when compared with the control group. AS group also demonstrated a trend toward reducing plasma concentration of LDH after exercise (P = 0.08), although not statistically significant. Allicin supplementation induced a higher value of TAC at rest, and this higher value was maintained 48 h after exercise, however, there was no difference in SOD values after exercise between the two groups. The results suggested that allicin might be a potential agent to reduce EIMD. Further studies concerning anti-inflammatory and anti-oxidative effects of allicin on EIMD are needed.